Induction of Tumor Necrosis Factor (TNF) Release from Subtypes of T Cells by Agonists of Proteinase Activated Receptors - Yang, Haiwei; Li, Tao; Wei, Jifu; Zhang, Huiyun; He, Shaoheng (Mediators of Inflammation, 2013)
Serine proteinases have been recognized as playing an important role in inflammation via proteinase activated receptors (PARs). However, little is known about the influence of serine proteinases and PARs on TNF secretion from highly purified T cells. We challenged T cells from human peripheral blood with serine proteinases and agonist peptides of PARs and measured the levels of TNF in culture supernatants by ELISA. The results showed that thrombin and trypsin, but not tryptase, stimulated approximately up to 2.5-fold increase in TNF release from T cells following 16 h incubation. Proteinase inhibitors and PAR-1 antagonist SCH 79797 almost completely abolished thrombin- and trypsin-induced TNF release from T cells. Agonist peptides of PAR-1, but not PAR-2 induced TNF release from T cells. Moreover, trypsin- and thrombin-induced upregulated expression of TNF was observed in CD4+, IL-4+, or CD25+ T cells, but not in IFN+ or IL-17+ T cells. The signaling pathways MAPK/ERK and PI3K/Akt are involved in the thrombin- and trypsin-induced TNF release from T cells. In conclusion, thrombin and trypsin can induce TNF release from IL-4+ and CD25+ T cells through activation of PAR-1 and therefore contribute to regulation of immune response and inflammation of the body.